Functional anatomy and feeding biomechanics of a giant Upper Jurassic pliosaur (Reptilia: Sauropterygia) from Weymouth Bay, Dorset, UK. Issue 2 (13th June 2014) - Foffa, Davide; Cuff, Andrew R.; Sassoon, Judyth; Rayfield, Emily J.; Mavrogordato, Mark N.; Benton, Michael J.
Abstract Pliosaurs were among the largest predators in Mesozoic seas, and yet their functional anatomy and feeding biomechanics are poorly understood. A new, well‐preserved pliosaur from the Kimmeridgian of Weymouth Bay (UK) revealed cranial adaptations related to feeding. Digital modelling of computed tomography scans allowed reconstruction of missing, distorted regions of the skull and of the adductor musculature, which indicated high bite forces. Size‐corrected beam theory modelling showed that the snout was poorly optimised against bending and torsional stresses compared with other aquatic and terrestrial predators, suggesting that pliosaurs did not twist or shake their prey during feeding and that seizing was better performed with post‐symphyseal bites. Finite element analysis identified biting‐induced stress patterns in both the rostrum and lower jaws, highlighting weak areas in the rostral maxillary‐premaxillary contact and the caudal mandibular symphysis. A comparatively weak skull coupled with musculature that was able to produce high forces, is explained as a trade‐off between agility, hydrodynamics and strength. In the Kimmeridgian ecosystem, we conclude that Late Jurassic pliosaurs were generalist predators at the top of the food chain, able to prey on reptiles and fishes up to half their own length.